Alcohol consumption and intoxication among people involved in police‐recorded incidents of violence and disorder in non‐metropolitan New South Wales - Shelley Rowe; John Wiggers; Melanie Kingsland; Craig Nicholas; Luke Wolfenden (Elsevier, 2012)
Abstract Objective: To describe, based on routinely recorded police data, the prevalence and characteristics of alcohol consumption among people involved in violence and disorder incidents in non‐metropolitan New South Wales (NSW). Methods: A descriptive analysis was conducted of people involved in violence and disorder incidents over 24 months (2003-05) across 21 non‐metropolitan police commands. The prevalence of alcohol involvement was reported as: the annual population rate of people involved in incidents who had consumed alcohol; the proportion of people involved in such incidents who had consumed alcohol; and the proportion of such people who were intoxicated. Variation in alcohol involvement was described by: geographic area; day of week; time of day; and location alcohol was last consumed. Results: Annually, one in 118 people in the population consumed alcohol prior to involvement in a violence incident, and one in 476 people did so prior to a disorder incident. At least 71% of such people were intoxicated. Late Saturday evening was the peak time for alcohol involvement. Prior drinking in private residences and licensed premises was associated with violence and disorder incidents (respectively). The prevalence of alcohol consumption rose with increased geographic remoteness. All characteristics displayed geographic variation. Conclusions: The high prevalence of alcohol consumption, particularly intoxication, in violence and disorder incidents represents a significant public health issue for non‐metropolitan NSW. Implications: Geographic variability in the prevalence and characteristics of alcohol‐related crime suggests a need for locally targeted, yet evidence‐based, interventions to reduce such harm.